InfoMax Bayesian learning of the Furuta pendulum - Jeni, László A.; Flórea, György; Lőrincz, András (Acta Cybernetica, 2008)
We have studied the InfoMax (D-optimality) learning for the two-link Furuta pendulum. We compared InfoMax and random learning methods. The InfoMax learning method won by a large margin, it visited a larger domain and provided better approximation during the same time interval. The advantages and the limitations of the InfoMax solution are treated.